ANALISIS DANA OTONOMI KHUSUS TERHADAP HUMAN DEVELOPMENT DAN PERTUMBUHAN EKONOMI DI KABUPATEN MERAUKE - Yuan Williamson Tamberan; Romualdus Turu Putra Maro Djanggo (Faculty Of Economics and Business, Musamus University, 2019)
This research aims to determine the effect of allocation of special Autonomy Fund in Education, special autonomy Fund in health education and special autonomy fund in the field of infrastructure education to economic growth directly or indirectly through the human development index in Merauke Regency. The type of data used is data time series and data collection is done by the documentation method. Data was analyzed using the simultaneous equation model approach with the help of SPSS Amos 21 software. The results showed that the special Autonomy fund variable has been positively significant to the economic growth directly, indirectly through the human development Index of Special Autonomy Fund fields Education is not significant to economic growth. Health special Autonomy fund variables and special autonomy fund infrastructure areas are directly significant to economic growth. Meanwhile, indirectly through human development index a variable of special autonomy fund in Health and Special Autonomy fund areas of infrastructure are positively significant to the economic growth Key words: Special autonomy, human development index, economic growth